HPLC quantification of two isomeric triterpenic acids isolated from Mitracarpus scaber and antimicrobial activity on Dermatophilus congolensis - Gbaguidi, A. Fernand; Accrombessi, Georges; MOUDACHIROU, MANSOUROU; Quetin-Leclercq, Joëlle (My University, 2005)
Oleanolic (OA) and ursolic acids (UA) were isolated for the first time from the alcoholic extract of Mitracarpus scaber possessing antimicrobial effects on Dermatophilus congolensis. These two triterpenic acids were also active (MIC 15 g/ml) on this causative agent of dermatophilosis in African animals. To quantify OA and UA in M. scaber, a new, simple and rapid high-performance liquid chromatography (HPLC) method compatible with MS detection was developed and validated. The mobile phase acetonitrile:H2O (85:15, v/v) was pumped through a C18 octadecylsilyl silica column at a flow rate of 0.6 ml/min and the eluate was monitored at 215 nm. The calibration curves constructed between 0.5 and 10 g/ml showed linear relationships with good R2 values. The developed method was precise and reproducible with relative standard deviations (RSD) for these two active constituents between 0.22–2.06% (intraday) and 1.61–3.72% (interday) for concentrations from 0.5 to 6 g/ml. Limits of detection and quantification were, respectively, 0.2 and 0.5 g/ml.
Keywords: HPLC; Mitracarpus scaber; Dermatophilus congolensis; Triterpenic acids